Necrotizing Soft Tissue Fasciitis after Intramuscular Injection - Angelica Abbate; Piero Luigi Almasio; Martina Mongitore; Gaetano Di Vita; Rosalia Patti (Case Reports in Surgery)
Necrotizing soft tissue fasciitis (NSTIs) or necrotizing fasciitis is an infrequent and serious infection. Herein, we describe the clinical course of a female patient who received a diagnosis of NSTIs after gluteus intramuscular injection. We also report the results of our review of published papers from 1997 to 2017. Since now, 19 cases of NSTIs following intramuscular injections have been described. We focus on the correlation between intramuscular injection and NSTIs onset, especially in immunosuppressed patients treated with corticosteroids, suffering from chronic diseases or drug addicted. Intramuscular injections can provoke severe tissue trauma, representing local portal of infection, even if correctly administrated. Otherwise, it is important not to inject drug in subcutaneous, which is a less vascularized area and therefore more susceptible to infections. Likewise, a proper injecting technique and aspiration prior to injection seem to be valid measure to prevent intra-arterial or para-arterial drug injection with the consequent massive inflammatory reaction. Necrosis at the infection site appears to be independent of the drug, and it is a strong additional risk factor for NSTIs.